Keterlaksanaan Program Magang Sekolah Penggerak dalam Rangka Implementasi Kurikulum Merdeka di Sekolah Dasar - halidjah, Siti; Kresnadi, Hery (Journal of Educational Review and Research, 2025)
The purpose of this study is to describe the implementation of the Driving School Internship Program in the context of the implementation of the Independent Curriculum at LKIA Pontianak Elementary School. This research is a qualitative descriptive research, the subject of the research is students of the 2023/2024 Driving School-IKM Internship group. The source of virginity is the results of interviews, observations, and document analysis. The research is carried out with the stages of planning, implementation, followed by data analysis, and then the preparation of a report. Data collection techniques are in the form of observation techniques and documentation studies with data collection tools in the form of interview guides, conservation sheets, and student report documents. The research that has been carried out has had a positive impact in order to support the Implementation of the Independent Curriculum at the elementary school level, students have the space to apply the knowledge gained in lectures to be applied in the context of actual learning.